2019
DOI: 10.1111/jicd.12453
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of student use of videos to support learning in a simulation laboratory course: A perception and analytics approach

Abstract: Aim This paper evaluates the use of online video learning materials used for a simulation laboratory course for 2 consecutive cohorts of students using an evaluation and analytics approach. Methods 100 online video clips were created to support students’ learning before, during and after the scheduled simulation laboratory teaching sessions in a fixed prosthodontics course. Videoed online presentations included screen‐captured PowerPoint presentations, simulation laboratory psychomotor and clinical skills demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…The presented data show the promising use of DE in an undergraduate dental curriculum. Our results are in line with those of a previous study that found that screen-captured lectures and video demonstrations were rated as highly useful by students regarding their self-perceived learning outcome in a course in Prosthodontics [12].…”
Section: Effectiveness Of Desupporting
confidence: 92%
See 1 more Smart Citation
“…The presented data show the promising use of DE in an undergraduate dental curriculum. Our results are in line with those of a previous study that found that screen-captured lectures and video demonstrations were rated as highly useful by students regarding their self-perceived learning outcome in a course in Prosthodontics [12].…”
Section: Effectiveness Of Desupporting
confidence: 92%
“…Most studies focusing on teaching preclinical and clinical dentistry used either virtual learning objects designed for single learning objectives [5][6][7][8], video demonstrations of practical procedures, or static PowerPoint presentations [9][10][11]. However, DE utilizing screen-captured lectures and video demonstrations was only reported in a single course in Prosthodontics [12]. Within the evaluation survey of this promising approach, students rated screen-captured lectures as highly useful for their self-perceived learning outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The use of videos has been an integral part of the psychomotor skill training. It offers advantageous properties such as standardised content delivery, close-up viewing, on-demand access, and control of playback functionality to allow students for skill training, note-taking, and knowledge assimilation (Botelho, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Video demonstrations of procedures have become increasingly popular in recent years due to their convenience, accessibility, and retrievability 6,7 . Interestingly, 79% (n = 338) of the students we surveyed who had access to faculty‐recorded videos also used YouTube videos for their operative dentistry learning.…”
Section: Discussionmentioning
confidence: 99%